Recovery of uranium from ferruginous Shale mineralization from Um Bogma formation, Egypt, via Duolite ES‐467 chelating resin. Issue 4 (18th February 2021) - Radwan, Hend A.; Gado, Mohamed A.; El‐Wahab, Zeinab H. Abd; El‐Sheikh, Enass M.; Faheim, Abeer A.; Taha, Rania H.
Abstract: The ferruginous shale iron content (27.5 %) is a serious problem that prevents the separation of uranium. Chemical dissolution of the ferruginous shale from Um Bogma Formation, Egypt, has been studied for the recovery of uranium using the acidic leaching method. Um Bogma representative sample assays 700 ppm of uranium as the element of interest. The effective dissolution parameters such as acid concentrations, solid/liquid addition ratio, leaching time, and leaching temperature were planned to investigate. It was found that The dissolution rate was greatly influenced by the studied dissolution factors. Analysis of the kinetic data showed that the dissolution mechanism is fitted well to shrinking core model within chemical reaction as a rate determining step. It was found that the recorded activation energy (Ea) of uranium dissolution is 205 kJ/mol. The uranium dissolution efficiency of 95.2 % has been achieved with optimized conditions of 250 g/L H2 SO4 ; 1 : 7 (S/L) phase ratio; 250 °C for 7 hours. Finally, the best‐controlling factors were applied for uranium separation from Um Bogma leach liquor to produce a uranium concentrate with 69.985 % uranium purity. Abstract :